The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/s1678-9946201759069
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in the revaccination program of hematopoietic stem cell transplantation recipients

Abstract: Hematopoietic stem cell transplant (HSCT) recipients should be routinely revaccinated after transplantation. We evaluated the difficulties met in the revaccination program and how a prospective and tailored follow-up could help to overcome these obstacles. HSCT recipients (n=122) were prospectively followed up and categorized into Group 1 (n=72), recipients who had already started the revaccination program, and Group 2 (n=50), recipients starting their vaccines. Whenever a difficulty was reported, intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 23 publications
(42 reference statements)
0
18
0
2
Order By: Relevance
“…In other institutions, increased efforts to educate patients and tailored follow ups have been identified as solutions to improve revaccination programmes. 5 In another study examining reasons for declined revaccinations, some cited reasons included time out from transplant, immunosuppressive therapy and prior adverse reactions. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other institutions, increased efforts to educate patients and tailored follow ups have been identified as solutions to improve revaccination programmes. 5 In another study examining reasons for declined revaccinations, some cited reasons included time out from transplant, immunosuppressive therapy and prior adverse reactions. 6 …”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that mailing personalised information packets on how to access and fund vaccinations may be an effective low-cost strategy to improve post-ASCT revaccination compliance. In other institutions, increased efforts to educate patients and tailored follow ups have been identified as solutions to improve revaccination programmes 5. In another study examining reasons for declined revaccinations, some cited reasons included time out from transplant, immunosuppressive therapy and prior adverse reactions 6…”
Section: Discussionmentioning
confidence: 99%
“…istration and application of the vaccines, in private clinics, CRIE, basic health units (UBS) or vaccination rooms (15) .…”
mentioning
confidence: 99%
“…According to a national study, delays in the revaccination program were observed in about 80% of the participants, the majority due to failures by the transplant center in referring the patient for vaccination or in the application of vaccines in the vaccination sites. The lack of compliance by the patient or guardian was observed in a small frequency (15). Therefore, it is clear that efforts to ensure the success of the revaccination program must focus mainly on educational activities at HSCT centers and on greater integration of HSCT centers with CRIE and vaccination sites.…”
mentioning
confidence: 99%
“…Existem recomendações para a vacinação após o transplante no nosso país (MINISTÉRIO DA SAÚDE, 2019;GARNICA et al, 2010;MACHADO, 2021), porém poucos estudos foram realizados para avaliar a implementação da vacinação (SILVA et al, 2017) e o que diz a respeito à resposta vacinal (MACHADO, 2004;MACHADO et al, 2002;ADATI et al, 2020).…”
Section: Discussionunclassified